Penerapan Teknik Foot Massage dalam Mengatasi Masalah Keletihan pada Pasien Chronic Kidney Disease (CKD) di Ruang Prabu Siliwangi Lantai 3 RSUD Gunung Jati Kota Cirebon - Nisa Adyaningsih; Marwati Marwati; Dedi Miswar Purnomo; Berlian Ayu (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Backgraund: Chronic Kidney Disease (CKD) is a progressive decline in kidney function that often causes fatigue. In Cirebon City, until October 2024, the number of CKD patients undergoing hemodialysis reached 1,268 procedures. Untreated severe fatigue can interfere with comfort, reduce physical activity, and decrease sleep quality. Fatigue management involves not only pharmacological therapy but also non-pharmacological approaches based on Evidence-Based Nursing Practice (EBNP), such as foot massage techniques. Objective: To determine changes in fatigue levels after foot massage intervention in CKD patients. Methods: This scientific paper is prepared as a nursing care report using EBNP, which includes data collection, nursing diagnosis, and intervention planning. Foot massage interventions are given for 30 minutes every day for 3 days. Fatigue intensity is measured using a fatigue scale before and after the intervention. Results: The results showed a decrease in fatigue scores from 38 (severe category) to 20 (mild category). Patients reported feeling less tired and weak, and better quality of rest. Conclusion & Recommendation: Foot massage is an effective non-pharmacological intervention to reduce fatigue. Nurses are advised to apply this method optimally, and patients can practice it independently.